Effects of Lindamood phoneme sequencing program (LIPS) on a bilingual student. (c2012) - Jurdi, Sarah A. (2012)
The purpose of this case study was to determine the effectiveness of Lindamood Phoneme Sequencing program (LiPS) on phonemic awareness (PA), reading, and spelling in a bilingual teenager diagnosed with dyslexia, and the extent of effectiveness on each skill. To that end, the researcher compared the student’s scores before and after the intervention on a number of standardized achievement tests. The intervention took place over a period of six weeks. Data was also gathered using the Intermediate-Grade Checklist for Teacher Observation of a Child’s Reading Skills before and after the intervention, informal interviews were also conducted with the student’s parents and English teacher before and after the intervention, and a journal was utilized to note the student’s performance during the observation and intervention sessions. The results showed that the intervention program considerably improved the target skills. There were important gains in the student’s phonemic awareness, reading, and spelling scores in the post assessment results, in addition to the feedback obtained from the class observation and the informal interviews. The results also showed that both PA and reading improved at a faster rate than spelling. Implications for teaching phonemic awareness and recommendations for future research are outlined.